Radiotherapy Patterns of Care for Locally-advanced Non-small Cell Lung Cancer in the Pre- and Post-durvalumab Era: A Region-wide Survey in a Japanese Prefecture. (30th December 2021) - Kubo, Nobuteru; Kobayashi, Daijiro; Iwanaga, Mototaro; Matsuura, Masana; Higuchi, Keiko; Eishima, Jun; Muramatsu, Hiroyuki; Okano, Naoko; Shioya, Mariko; Onishi, Masahiro; Aoki, Tetsuya; Oike, Takahiro; et al.
Abstract: The promising results of the PACIFIC study led to the approval of consolidation durvalumab for coverage by the National Health Insurance (NHI) in 2018 for patients with locally-advanced unresectable non-small cell lung carcinoma (NSCLC) treated with definitive concurrent chemoradiotherapy (CCRT). However, the effect of NHI coverage on the patterns of care for this population remains unclear. Here, we conducted a questionnaire-based survey to determine the patterns of care for patients with stage II–III NSCLC treated with definitive radiotherapy in 2017 (pre-durvalumab era) or in 2019 (post-durvalumab era). Data were obtained from 11 radiotherapy facilities in Gunma prefecture, which has a population of 1.94 million. We identified 80 and 83 patients with stage II–III NSCLC who received definitive radiotherapy in Gunma in 2017 and 2019, respectively. At a given facility, CCRT was the treatment of choice in a significantly greater proportion of patients in 2019 than in 2017 (66% ± 20% vs 51% ± 29%, P  = 0.041). Intensity-modulated radiotherapy (IMRT) was more frequent in 2019 than in 2017 (24% vs 1.2%). Carboplatin plus paclitaxel was used for CCRT at higher rate in 2019 than in 2017 (73% vs 44%). Consolidation durvalumab was performed in 73% (40/55) of CCRT-treated patients in 2019, and the treatment was performed for the planned 12 months in 45% (18/40) of patients. These data indicate that NHI coverage of durvalumab might be a possible reason for choosing CCRT in patients with stage II–III NSCLC in the real-world setting.